Iron geochemistry in tropical estuarine soils affected by anthropic and natural disasters - Queiroz, Hermano Melo (2021)
Iron (Fe) is one of the most abundant and dynamic elements on Earth. It is present in rocks, minerals, soils, oceans, and is an essential element for virtually all living beings on terrestrial ecosystems. Due to its dynamics in the environment, Fe arouses the interest of several science fields. For soil science, the importance of this element is mostly related with its ability to interact with various chemical elements. In this sense, the Fe biogeochemical cycle is directly associated with cycles of other elements such as carbon (C), phosphorus (F), sulfur (S), and heavy metals. In estuarine soils, Fe geochemistry is marked by a dynamic equilibrium ruled by the redox oscillations active in these environments. However, anthropic or natural disturbances may affect the Fe geochemical behavior and consequently the fate of other associated elements (e.g., C, P, S, and metals). In this sense, this study had as objectives: (i) to study the Fe geochemistry in tropical estuarine soils affected by both anthropic and natural impacts and (ii) to assess the control of Fe geochemistry over the dynamic of other elements, such as trace metals, P, S, and C. To achieve these objectives, two tropical estuaries, affected by anthropic (i.e., affected by iron tailing deposition) and natural (massive mangrove dieback) disasters were evaluated. We observed a significant change in physicochemical conditions of soils after a massive mangrove forest mortality. The soils from dead mangroves changed from a chiefly anoxic environment to a suboxic environment. This change resulted in a decrease by 50% in the soils Fe contents. The Fe losses were mostly associated with the pyrite and low crystallinity Fe oxyhydroxides fractions. In addition, we estimated a loss of 170 tons of Fe from the 500 hectares of dead mangrove forests. Ultimately, the pyritization process was deeply compromised and therefor the capacity of mangrove forests to provide ecosystem services such as pollutant (i.e., metals) retention and carbon sequestration. In another scenario, the Rio Doce estuary received about 60 million m3 of Fe-rich tailings after Fundão dam rupture. The Fe biogeochemical behavior controlled the fate of metals, P, and the pedogenesis of estuarine soils after this event recognized as the world\'s largest mining disaster. The tailings, mostly composed of high crystallinity Fe oxyhydroxides (e.g., goethite and hematite), were transported 600 km downstream towards the estuary. Throughout this path, the tailings acted as a carrier of contaminants (e.g., metals) and large amounts of P. An expressive increase of P and metals contents in the estuarine soils were observed after the arrival of the tailings. These pollutants were predominantly associated with Fe oxyhydroxides. Over time, the tailings\' deposition favored the establishment and growth of plants which promoted a soil C input and drastic physicochemical changes. These changes resulted in a reducing environment favorable to microbial Fe reduction and an increase of low crystallinity Fe forms (e.g., ferrihydrite and lepidocrocite). These conditions led to the reductive dissolution of Fe oxyhydroxides, Fe losses, and an increased bioavailability of metals. Among the studied metals, manganese (Mn) showed the highest losses in the soil and an increase of 880% in the estuarine water. The increase in Mn bioavailability led to an increase of Mn levels in the liver and muscles of fish commonly consumed by the local population. The newly established Fe dynamic triggered massive Mn releases and high contamination risks. In this context, a similar behavior was observed for P. The changes associated with the dissimilatory Fe reduction led to an increase of readily available P in the estuarine soils and water. Moreover, our results indicate that Fe oxyhydroxides are a continuous source of dissolved P for the ecosystem, and that the Fe-rich tailings deposited in the estuarine ecosystem may be linked to a potential eutrophication process. Nevertheless, within four years after the disaster, the vegetation growth on the deposited tailings triggered the soil formation in the estuary. Different pedogenetic processes were described and evidenced (e.g., melanization, bioturbation, incipient paludization, and gleization). The newly formed Technosol showed evidences of potentially providing ecosystem services such as carbon sequestration and nutrient cycling that were previously unprovided in the estuary. In response to the biogeochemical changes, we observed a massive Fe loss from the estuarine soils which may represent an important Fe source from the estuary to the ocean waters. The Fe input into oceans (i.e., Fe ocean fertilization) is directly associated with marine productivity and the providing of services such as carbon sequestration. Thus, this study brings a novel approach to how anthropic or natural impacts may alter Fe dynamics in coastal ecosystems and how this affects the cycles of other important elements both to the estuary and the adjacent environments.